Mercury Exposure in Young Adulthood and Incidence of Diabetes Later in Life: The CARDIA Trace Element Study - He, Ka (American Diabetes Association, 2013)
OBJECTIVE: Laboratory studies suggest that exposure to methylmercury at a level similar to those found in fish may induce pancreatic islet β-cell dysfunction. Few, if any, human studies have examined the association between mercury exposure and diabetes incidence. We examined whether toenail mercury levels are associated with incidence of diabetes in a large prospective cohort. RESEACH DESIGN AND METHODS: A prospective cohort of 3,875 American young adults, aged 20–32 years, free of diabetes in 1987 (baseline), were enrolled and followed six times until 2005. Baseline toenail mercury levels were measured with instrumental neutron-activation analysis. Incident diabetes was identified by plasma glucose levels, oral glucose tolerance tests, hemoglobin A1C levels, and/or antidiabetes medications. RESULTS: A total of 288 incident cases of diabetes occurred over 18 years of follow-up. In multivariate analyses adjusted for age, sex, ethnicity, study center, education, smoking status, alcohol consumption, physical activity, family history of diabetes, intakes of long-chain n-3 fatty acids and magnesium, and toenail selenium, toenail mercury levels were positively associated with the incidence of diabetes. The hazard ratio (95% CI) of incident diabetes compared the highest to the lowest quintiles of mercury exposure was 1.65 (1.07–2.56; P for trend = 0.02). Higher mercury exposure at baseline was also significantly associated with decreased homeostasis model assessment of β-cell function index (P for trend < 0.01). CONCLUSIONS: Our results are consistent with findings from laboratory studies and provide longitudinal human data suggesting that people with high mercury exposure in young adulthood may have elevated risk of diabetes later in life.